2007
DOI: 10.1099/jmm.0.46965-0
|View full text |Cite
|
Sign up to set email alerts
|

Interpretive criteria to differentiate low- and high-level mupirocin resistance in Staphylococcus aureus

Abstract: Meticillin-resistant Staphylococcus aureus isolates were classified into three mupirocin susceptibility groups by the disc diffusion method using 5 and 200 μg mupirocin discs. The zone diameter observed for a 5 μg disc distinguished MupS from the resistant strains (either MupRL or MupRH). On the other hand, a 200 μg disc distinguished the high-resistance MupRH strains from the other two (MupS or MupRL). Thus, the concomitant use of 5 and 200 μg mupirocin discs allowed the clear distinction among the three mupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Until recently, methods for testing topical agents have not been included in susceptibility testing documents published by the Clinical and Laboratory Standards Institute (CLSI; formerly NCCLS), although guidelines for testing by various methods have been suggested by others (9,10,12,13,16,17). The British Society for Antimicrobial Chemotherapy has formal recommendations for the testing of mupirocin (www.bsac .org.uk) that include testing of a 5-g and a 20-g mupirocin disk.…”
mentioning
confidence: 99%
“…Until recently, methods for testing topical agents have not been included in susceptibility testing documents published by the Clinical and Laboratory Standards Institute (CLSI; formerly NCCLS), although guidelines for testing by various methods have been suggested by others (9,10,12,13,16,17). The British Society for Antimicrobial Chemotherapy has formal recommendations for the testing of mupirocin (www.bsac .org.uk) that include testing of a 5-g and a 20-g mupirocin disk.…”
mentioning
confidence: 99%
“…However, the mupirocin susceptibility testing was not preconized by CLSI, so the results for this antibiotic were interpreted as previously described (7,9). The methicillin resistance was also evaluated by other phenotypic methods, such as the MIC for oxacillin (5), the MicroScan, and PCR of the mecA gene (6).…”
mentioning
confidence: 99%
“…Palepou et al [8] 25 /xg de Oliveira et al [9] 5 /"g 200 /*g Zone-of-inhibition diameter, by susceptibility level zone-of-inhibition diameter, but were also classified as being mupirocin susceptible, on the basis of MICs using the Etest. Our study demonstrated that there was a high prevalence of mupirocin resistance among MRSA clinical isolates, compared with other surveillance studies that found a geographic variation in the prevalence of mupirocin resistance among MRSA isolates that ranged from 4% to 17%.…”
Section: Jigmentioning
confidence: 99%